Tinjauan Yuridis Penegakan Hukum Terhadap Tindak Pidana Perdagangan Orang Dalam (Insider Trading) Berdasarkan Perspektif Hukum Positif di Indonesia - Pasaribu, Theresa Maya Avila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The capital market acts as a source of financing for businesses and an investment vehicle for the community, demanding transparency of information so that investors can make the right decisions. Unfortunately, this principle is often disrupted by insider trading, which is detrimental to transparency. This study, using normative and analytical descriptive legal methods, found that criminal law enforcement against insider trading is hampered by evidence, lack of Bapepam-LK's ability to identify, and a tendency to only impose administrative sanctions. Efforts to overcome this by Bapepam-LK are considered ineffective and need to be improved, both penally and non-penally, to minimize insider trading.